PENGUATAN SIKAP KERJA SAMA MELALUI TUGAS SUSUN KATA BERKELOMPOK PADA MATERI KALIMAT MAJEMUK BERTINGKAT DI SDN PERCOBAAN 2 KOTA MALANG - Rina Sari (Universitas Negeri Malang, 2024)
Strengthening cooperative attitudes through group assignments has become an important approach in facilitating understanding of complex material in elementary schools, especially in the context of learning multilevel compound sentences. This research was conducted at SDN Percobaan 2 Kota Malang with a focus on implementing group assignments in Indonesian language subjects to understand and apply graded compound sentence material. The research method used is a literature review, where data is collected from literature sources relevant to the research topic. The purpose of this research is to evaluate the effectiveness of group assignments in improving understanding and application of material and strengthening students' cooperative attitudes. The results of the discussion show that group assignments are effective in strengthening student cooperation with the support of factors such as teacher support, group diversity, student motivation, development of social skills, and a supportive school culture. By paying attention to these factors, group assignments can be an effective method in overcoming difficulties in understanding material and promoting cooperation and collaboration among students. Therefore, the group assignment approach at SDN Percobaan 2 Kota Malang shows great potential in improving the quality of Indonesian language learning, especially in graded compound sentence material.